Variation in apical hook length reflects the intensity of sperm competition in murine rodents - Šandera, Martin; Albrecht, Tomáš; Stopka, Pavel (PloS one, 2013)
BACKGROUND: Post-copulatory sexual selection has been shown to shape morphology of male gametes. Both directional and stabilizing selection on sperm phenotype have been documented in vertebrates in response to sexual promiscuity. METHODOLOGY: Here we investigated the degree of variance in apical hook length and tail length in six taxa of murine rodents. CONCLUSIONS: Tail sperm length and apical hook length were positively associated with relative testis mass, our proxy for levels of sperm competition, thus indicating directional post-copulatory selection on sperm phenotypes. Moreover, our study shows that increased levels of sperm competition lead to the reduction of variance in the hook length, indicating stabilizing selection. Hence, the higher risk of sperm competition affects increasing hook length together with decreasing variance in the hook length. Species-specific post-copulatory sexual selection likely optimizes sperm morphology.
Keywords: spermie; myši; Selection, Genetic; velikost orgánu; bičík spermie; selekce (genetika); hlavička spermie; Male; Spermatozoa; Animals; Sperm Tail; Mice; Testis; mužské pohlaví; Organ Size; Sperm Head; zvířata; testis